Analisis Penyebaran Penyakit Covid-19 dengan Pengaruh Pengobatan Isolasi Mandiri dan Pengobatan Perawatan Rumah Sakit (Studi Kasus Penyebaran di DKI Jakarta) - Adam Victorio Alexis; Fariani Hermin Indiyah; Eti Dwi Wiraningsih (Program Studi Matematika Universitas Negeri Jakarta, 2022)
In this research, a model for the spread of Covid-19 will be built using a differential equation because in the population there are two subpopulations who can spread the disease, there is one subpopulation who go through incubation period, and there are also 2 subpopulations who go through the treatment so the model will consists of compartments such as susceptible, exposed, asymptomatically infectious, symptomatically infectious, treatment 1 (self-isolation), treatment 2 (hospital care), and recovered. Analysis begins by calculating the disease-free equilibrium and endemic equilibrium. Before stability analysis, the model must be checked for adequacy in describing the disease spread. Stability analysis begins by forming the next generation matrix of the model with helps of jacobian matrix and chracteristic equation, then we can get basic reproduction number. By entering the value of parameters according to data to the basic reproduction number, we get reproduction number is 0,851115. The size of reproduction number means that the disease will disappear from the population.